2020
DOI: 10.1016/j.jtcme.2019.10.002
|View full text |Cite|
|
Sign up to set email alerts
|

Wound healing efficacy of Jamun honey in diabetic mice model through reepithelialization, collagen deposition and angiogenesis

Abstract: Diabetic patients are frequently afflicted with impaired wound healing where linear progression of molecular and cellular events compromised. Despite of meaningful progress in diabetic treatment, management of diabetic chronic wounds is still challenging. Jamun ( Syzygium cumini ) honey may be a promising candidate for diabetic wound healing and need to explore in detail. So present study was designed to evaluate the efficacy of Jamun honey (JH) for diabetic wound healing in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…This dynamic process is strongly regulated by signals from serum and the surrounding extracellular matrix environment [ 67 ]. Stimulation of angiogenesis by honey was demonstrated in an in vitro study with analogues of angiogenesis and an endothelial proliferation assay [ 68 ], and more recently, in another in vivo-model study [ 69 ].…”
Section: The Mechanisms Of Honey In Wound and Burn Healingmentioning
confidence: 99%
“…This dynamic process is strongly regulated by signals from serum and the surrounding extracellular matrix environment [ 67 ]. Stimulation of angiogenesis by honey was demonstrated in an in vitro study with analogues of angiogenesis and an endothelial proliferation assay [ 68 ], and more recently, in another in vivo-model study [ 69 ].…”
Section: The Mechanisms Of Honey In Wound and Burn Healingmentioning
confidence: 99%
“…85 In another study, researchers isolated primary fibroblasts from diabetic and nondiabetic animals, created scratch wounds, and examined their migratory behavior when treated with jamun honey and manuka honey. 86 Interestingly, nondiabetic mice-derived fibroblasts exhibited an increased wound closure rate under both types of honey dilutions in comparison with the untreated fibroblasts, but this was not the case for fibroblasts derived from diabetic mice. However, cell migration was increased for fibroblasts derived from diabetic and nondiabetic animals after treatment with jamun and manuka honey when compared to untreated cells.…”
Section: In Vitro Wound Healing Effectsmentioning
confidence: 91%
“…Moreover, honey-treated fibroblasts derived from both diabetic and nondiabetic mice exhibited an up-regulation of alpha-smooth muscle actin expression, which is a marker of prime myofibroblasts and of collagens I and III. 86 In another in vitro study, researchers used a human fibroblast cell line and examined the wound healing effects of acacia, buckwheat, and manuka honey after creating wounds with the scratch assay. 87 Cells exposed to all 3 types of honey showed higher wound closure rates when compared to untreated cells, while the number of migrating cells was also higher in the presence of all types of honey.…”
Section: In Vitro Wound Healing Effectsmentioning
confidence: 99%
“…The study concluded that Jamun had similar efficacy to the already approved Manuka honey. 88 With additional testing, this has the potential to rapidly accelerate the wound repair process.…”
Section: Potential Therapeutic Agents For Diabetic Wound Healingmentioning
confidence: 99%